KEHIDUPAN PEREMPUAN PETANI KARET DI DESA LUKUN KECAMATAN TEBING TINGGI TIMUR KABUPATEN KEPULAUAN MERANTI PROVINSI RIAU - Ria Sri Utami; Ashaluddin Jalil (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Being a women as a rubber tapper forrural housewives is common. this is the same as that of women in Lukun village, Tebing Tinggi Timur District, Meranti Islands Regency, Riau Province. Obtain a factual description of the socio-economic conditions of female households as rubber farmers manage their households. The method used is a qualitative method with interview techniques in gathering data and information. The results of the analysis found that the socio-economic conditions of rubber farming female households have different levels of welfare. Where the more socioeconomic activities of thesewomen, the level of household welfare is high. Vice versa if the woman is only dependent on one economic activity, the level of household welfare is low. With all the conditions of limitations they have, they can still send their children to school. Keywords: Rubber Tappers, Social Economy, A Flow Of Time.